THE ROLE OF THE NGARUAT KAMPUNG TRADITION IN ENHANCING ECOLOGICAL AWARENESS IN RANJENG VILLAGE, GARUT - Alika Nurhasanah; Ahmad Isnaeni; Nurul Isnaini; Muslimin Muslimin (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2026)
The Ngaruat Kampung tradition represents a form of local wisdom that strengthens ecological awareness among the residents of Kampung Ranjeng, Garut Regency. This tradition is performed to express gratitude to God, honor ancestors, and maintain harmony between humans and nature. The research explores the meanings, functions, and ecological values inherent in the Ngaruat Kampung tradition, as well as its contribution to environmental conservation. A qualitative approach utilizing ethnographic methods was employed. Data collection involved participant observation, in-depth interviews with traditional leaders and community members, and documentation. Qualitative data were organized and analyzed thematically using NVivo 15 to identify patterns, categories, and relationships among the findings. The results indicate that the Ngaruat Kampung tradition embodies ecological values through various ritual activities, such as respect for natural resources, environmental cleanliness, preservation of water sources, and reinforcement of social norms that promote environmental stewardship. Additionally, the tradition serves as a medium for transmitting environmental knowledge to younger generations through symbols, traditional advice, and collective community practices. The findings demonstrate that Ngaruat Kampung holds cultural and spiritual significance and plays a crucial role in fostering ecological awareness within the community. Preserving this tradition is therefore an effective strategy for supporting sustainable development based on local wisdom.